2018
DOI: 10.1038/s41598-018-29156-5
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in pleural effusions of pulmonary adenocarcinoma and survival prediction: a controlled study by pleural biopsy

Abstract: PD-L1 expression in pleural effusions (PE) of lung adenocarcinoma (ADC) was compared with pleural biopsies and the positive expression in PE was correlated with survival time. The matched slices from same patient’s pleura and PE were collected which both were pathologically verified positive. Immunohistochemistry (IHC) was used to detect PD-L1 expression. A total of 51 eligible cases were enrolled, including 30 males and 21 females. The average age was (67.06 ± 12.10) years. PD-L1 expression wasn’t statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…At present, the difficulties associated with performing biopsies hamper glioma diagnosis and therapeutic intervention, highlighting the need to discover non-invasive or minimally invasive biomarkers for early diagnosis and correct stratification (31). sPD-L1 can be detected in biofluids, providing a novel diagnostic test for a variety of tumors (32)(33)(34). In our previous study, elevated sPD-L1 levels in the serum were observed in preoperative patients with HGG.…”
Section: Discussionmentioning
confidence: 97%
“…At present, the difficulties associated with performing biopsies hamper glioma diagnosis and therapeutic intervention, highlighting the need to discover non-invasive or minimally invasive biomarkers for early diagnosis and correct stratification (31). sPD-L1 can be detected in biofluids, providing a novel diagnostic test for a variety of tumors (32)(33)(34). In our previous study, elevated sPD-L1 levels in the serum were observed in preoperative patients with HGG.…”
Section: Discussionmentioning
confidence: 97%
“…A growing number of studies have now examined the variability of PD‐L1 expression between different types of NSCLC specimens, which include bronchial washings, aspirates of the primary tumor or its metastases (including cells from pleural and pericardial fluids), endoscopic and transthoracic needle biopsies, incisional biopsies of tumor deposits (usually in skin or superficial lymph nodes), and entire resected tumors . Unfortunately, the specimens compared in these studies have almost always differed not only in their nature (cytology vs histology) but also in their site of origin, and the well‐documented heterogeneity of PD‐L1 expression within and between tumor deposits has made the precise basis of any variability difficult to determine.…”
Section: Discussionmentioning
confidence: 99%
“…Although much has now been published about the variability of PD‐L1 expression between different types of specimens of NSCLC, little attention has been paid specifically to the important question of the effect of fixation. In view of this, we thought it would be of value to determine whether there is any difference in PD‐L1 expression between EBUS‐guided aspirates of NSCLC fixed in alcohol‐based fixatives and those fixed in NBF, the standard laboratory fixative for histology specimens.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 PD-L1 expression in pleural effusions compared with pleural biopsies in the same patient by IHC was studied by Xu et al 35,36 In total, 51 cases were reviewed with no difference detected in expression with a threshold of at least 10% PD-L1 expression (65 vs. 65%). 29 However, a difference was detected when a threshold of >50% expression was utilized (12 vs. 24%, p ¼ 0.007) with higher detection in the pleural biopsy specimen. Heymann et al also compared PD-L1 expression in 214 specimens collected from 188 patients with NSCLC among cytology, small biopsy, and surgically resected biopsies, and reported that PD-L1 testing done on pleural fluid samples had an accuracy of 77% compared with histological samples.…”
Section: Molecular Targets In Pleural Effusionsmentioning
confidence: 95%
“…15 Although the rate of detection was higher in tissue samples (34%) compared with MPE (30%), the difference was not statistically different. [26][27][28][29] Carter et al analyzed 27 cases of NSCLC with MPE after excluding 14 cases due to inadequate tumor cellularity and detected a genetic aberration in 59% of samples (AKT, BRAF, EGFR, ERBB2, KRAS, NRAS, PIK3CA). 17,30 Liu et al evaluated 192 advanced cases of NSCLC with both primary tumor and MPE samples for EGFR with no difference in detection at 62 and 59%, respectively.…”
Section: Molecular Targets In Pleural Effusionsmentioning
confidence: 99%